REPRESENTASI DAN DINAMIKA NILAI KULTUR DALAM NOVEL ANAK RANTAU KARYA AHMAD FUADI: KAJIAN ANTROPOLOGI SASTRA CLIFFORD GEERTZ - Annisa Putri Achmad; Suarni Syam Saguni; Baharman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the representation and dynamics of cultural symbolic meanings through plans, recipes, rules, and instructions based on the anthropological perspective of Clifford Geertz. This research employs a qualitative method in the form of a library study with a descriptive-interpretative design. The data consist of excerpts containing representations and dynamics of cultural values in the novel Anak Rantau by Ahmad Fuadi. Data were collected through reading, note-taking, and documentation techniques, and analyzed using the stages proposed by John W. Creswell, including data reduction, classification, description, interpretation, and conclusion drawing. The results show that the representation of plans appears in personal actions such as repairing a house and earning a living, with dynamics reflected in the expansion of cultural symbolic meanings that adapt to changing times. The representation of recipes is seen in the use of the surau as temporary housing and economic strategies such as working in small shops and workshops, with dynamics indicating a shift from sacred to functional roles. The representation of rules is reflected in the prohibition of same-clan marriage as a means of maintaining kinship order, which later negotiates with individual freedom and tolerance values. Meanwhile, instructions are represented in the philosophy of alam takambang jadi guru and the principle of adat bersendi syarak, syarak bersendi kitabullah, with dynamics seen in their reinterpretation by modern generations. Overall, culture in the novel functions as a dynamic mechanism of control that continuously evolves. Keywords: novel, literary anthropology, dynamics, cultural values, representation